Reading Contemporary Indonesian Muslim Women Writers Representation, Identity and Religion of Muslim Women in Indonesian Fiction - Arimbi, Diah Ariani (ICAS Publications Series, 2009)
Most literary analysis of the canon of Indonesian literature overlooks its religious aspect. This book is the first to discuss the construction of gender and Islamic identities in literary writing by four prominent Indonesian Muslim women writers: Titis Basino P I, Ratna Indraswari Ibrahim, Abidah El Kalieqy and Helvy Tiana Rosa. The narratives of the four writers are rich sources for revealing the construction of Indonesian Muslim women's identities. Within their feminist reading the writers understand that gender roles are negotiable rather than inherent. In representing women in a variety of discourses they draw multi-faceted women struggling against repression and domination, and resisting their status as powerless.